2001
DOI: 10.1046/j.1365-2958.2001.02322.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Bacillus subtilis fatty acid desaturase in membrane adaptation during cold shock

Abstract: SummaryIn our attempt to understand the cold shock response of Bacillus subtilis, we report on the role of the B. subtilis fatty acid desaturase (FA-D) Des during membrane adaptation to low temperatures and demonstrate its importance during cold shock. A des null mutant was constructed and analysed in comparison with its parental strain. Growth studies and large-scale comparative fatty acid (FA) analysis revealed a severe cold-sensitive phenotype of the des deletion mutant during the absence of isoleucine and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
82
1
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(92 citation statements)
references
References 22 publications
7
82
1
2
Order By: Relevance
“…thesis of all four unsaturated FA species so far detected in this bacterium (Weber et al 2001a). Although earlier investigations assigned B. subtilis desaturase activity to a membrane-associated enzyme of the acetyl-CoA-desaturase type (Dunkley et al 1991), it has now become clear that this enzyme is a lipid desaturase .…”
Section: Membrane Adaptationmentioning
confidence: 86%
See 2 more Smart Citations
“…thesis of all four unsaturated FA species so far detected in this bacterium (Weber et al 2001a). Although earlier investigations assigned B. subtilis desaturase activity to a membrane-associated enzyme of the acetyl-CoA-desaturase type (Dunkley et al 1991), it has now become clear that this enzyme is a lipid desaturase .…”
Section: Membrane Adaptationmentioning
confidence: 86%
“…As such, it modifies the lipids present in the membrane directly at the time of cold shock, thereby providing a rapid-responding system for the modulation of membrane fluidity. Interestingly, in the absence of exogenous isoleucine sources, deletion of des in a B. subtilis strain JH642 background results in a cold-sensitive growth phenotype, indicating an important role for this enzyme during cold adaptation (Weber et al 2001a). In such a mutant, artificial expression of des in trans does not only cure the observed phenotype but demonstrates that Des possesses cryoprotective properties that significantly increase the cold tolerance of B. subtilis (Weber et al 2001a).…”
Section: Membrane Adaptationmentioning
confidence: 99%
See 1 more Smart Citation
“…Mga2p is a key transcription factor that controls expression of Ole1, the sole fatty acyl desaturase in S. cerevisiae responsible for conversion of the saturated fatty acids stearate (C18) and palmitate (C16) to oleate and palmitoleate, respectively (Zhang et al 1999;Chellappa et al 2001). The ratio of saturated to unsaturated fatty acids (UFA/SFA) is known from studies of Bacillus subtilis, for example, to be a key determinant of membrane fluidity (Grau and de Mendoza 1993;Weber et al 2001). Suutari et al (1990), however, showed that the UFA/SFA ratio of Saccharomyces is unaffected by growth temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, during the study the steady-state growth at 4 C transcription increased about 10-fold and led to enhancing the level of protein expression. Weber et al (2001) (29) suggested that cold shock led to chromosome compaction due to a decrease in the transcriptional and translational capacity of the cell. Immunofluorescence electron microscopy confirmed that CSPs were localized around the nucleoid and that the zone of localization increases concomitant with nucleoid compaction.…”
Section: Discussionmentioning
confidence: 99%